Oncological Care During First Peruvian National Emergency COVID-19 Pandemic: A Multicentric Descriptive Study - Valdiviezo, Natalia (2022)
Purpose: The aim of this study is to evaluate the oncological care during the first state of national emergency due to the COVID-19 pandemic in several public cancer hospitals in Peru. Materials and Methods: A multicentric cross-sectional descriptive study was conducted by interviewing adult cancer patients diagnosed and treated between January 2019 and February 2020 from 18 hospitals. This study was carried out in September 2020, the last month of the first state of national emergency. Demographic and clinical characteristics were evaluated, including COVID-19 status and cancer treatment features. Results: A total of 1472 patients were included; the median age was 55 years (range 19–97). Most patients (85.8%, n = 1263) had solid neoplasia, 13.5% (n = 198) hematologic neoplasia, and 0.7% (n = 11) others. SARS-CoV-2 infection was confirmed in 8.6% (n = 126), 1.2% (n = 18) were probable, 1.6% (n = 24) suspected, and 88.6% (n = 1304) negative cases. Overall, 51.6% of patients (n = 759) had cancer treatment delays, 42.5% (n = 626) changed treatment delivery (endovenous to oral systemic therapy), and 12.6% (n = 185) of cases cancer therapy was discontinued. In total, 10.3% (n = 117) of patients whose disease was controlled or in remission, experienced progression of disease during the state of emergency. A total of 6.7% (n = 98) of patients died, of whom 73.5% (n = 72) died from disease progression; 18.4% (n = 18) from SARS-CoV-2 infection and 8.1% (n = 8) from undetermined causes. Patients with hematological malignancies [hazard ratio (HR): 5.11 (95% confidence interval (CI): 1.99–13.07)] and no response to therapy before the onset of the pandemic [5.01 (1.44–17.42)] had an increased risk of death among COVID-19 infected individuals, whereas advanced clinical stage [5.09 (2.37–10.95)] and discontinuation of treatment [3.66 (1.97–6.78)] were risk factors among non-COVID-19 patients. Conclusion: Our study suggests that the COVID-19 pandemic has an adverse impact on the outcomes of Peruvian cancer patients. In our cohort, cancer mortality was higher than COVID-19 disease mortality.